Jezus jako zelota według Rezy Aslana. Prezentacja i krytyka - Artemiuk, Przemysław (Studia Teologiczne Białystok Drohiczyn Łomża, 2023)
In the article, the author shows the vision of Jesus presented by R. Aslan. This Muslim historian of religion, publicist, television commentator and presenter treats Jesus as a zealous Jew – a zealot and a revolutionary. In this way, it fits into the trend of the third search for the historical Jesus. However, it shows the story of the Nazarene in aspects. Undertaking the analysis of the work of a Muslim, the author of the article draws attention to the methodological assumptions and shows the main threads of Jesus' life in the light of his research. In the last part of the article, he assesses the proposed image, referring to fragments of P. Lisicki’s work and R. Barron’s essay on the book of the Muslim researcher. The image of Jesus presented by R. Aslan is constructed under a predetermined thesis. The Muslim researcher includes the Nazarene in his own vision, which he creates earlier, referring to the historical context. R. Aslan uses false hermeneutics. The Muslim researcher selectively treats the texts of the Gospels. From all the New Testament writings, he chooses those that will confirm his thesis. The vision of the American researcher reveals a certain naivety and lack of science. Although R. Aslan invokes various biblical authorities, at the same time he behaves as if he completely disregards the results of specialists' research. He argues that he discovers a historical, pre-Christian Jesus who was completely falsified by the followers of Christ. He declares trust in history and a new attempt to read the Gospel, while he acts completely differently.